2012
DOI: 10.1111/exd.12003
|View full text |Cite
|
Sign up to set email alerts
|

Morphogenesis of chimeric hair follicles in engineered skin substitutes with human keratinocytes and murine dermal papilla cells

Abstract: Engineered skin substitutes (ESS) have been used successfully to treat life-threatening burns, but lack cutaneous appendages. To address this deficiency, dermal constructs were prepared using collagen-glycosaminoglycan scaffolds populated with murine dermal papilla cells expressing green fluorescent protein (mDPC-GFP), human dermal papilla cells (hDPC) and/or human fibroblasts (hF). Subsequently, human epidermal keratinocytes (hK) or hK genetically modified to overexpress stabilized b-catenin (hK') were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 21 publications
(21 reference statements)
0
33
0
Order By: Relevance
“…Sriwiriyanont et al [59] observed neofollicles in grafted engineered skin substitutes with human epidermal keratinocytes and murine dermal papilla cells but not when the dermal cells were of human origin. In other study [60], they grafted in nude mice, chimeric populations of cultured human keratinocytes from neonatal foreskins and cultured murine dermal papilla cells from adult green fluorescent protein transgenic mice.…”
Section: Discussionmentioning
confidence: 99%
“…Sriwiriyanont et al [59] observed neofollicles in grafted engineered skin substitutes with human epidermal keratinocytes and murine dermal papilla cells but not when the dermal cells were of human origin. In other study [60], they grafted in nude mice, chimeric populations of cultured human keratinocytes from neonatal foreskins and cultured murine dermal papilla cells from adult green fluorescent protein transgenic mice.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Lefkowitz et al demonstrated the presence of miRNAs in the hair shafts although they do not have nuclear components (7,8). We also reported that the hair miRNA levels did not correlate with serum miRNA levels (9), suggesting that they can be independent biomarkers.…”
Section: Question Addressedmentioning
confidence: 48%
“…Peripheral artery occlusive disease is an uncommon symptom in EDS IV, although fragility of the large vessels and easy bruising are well documented (3)(4)(5)(6)11,12). In an earlier report using intravital capillaroscopy and fluorescence videomicroscopy, SupertiFurga et al (13) described microangiopathy of the skin capillaries, with microbleedings and microaneurysms indicating that EDS IV might not only be restricted to the large vessels.…”
Section: Resultsmentioning
confidence: 99%
“…The clinical diagnosis of EDS IV is made according to the 1997 Villefranche nosology defining major and minor diagnostic criteria (5). The underlying defect is a mutation in the COL3A1 gene located on the long arm of chromosome 2, in ª 2013 John Wiley & Sons A/S Experimental Dermatology, 2013, 22, 216-238 position 2q24.3-q31 that encodes the pro-a1 chain of type III collagen (3)(4)(5)(6). The resulting impaired function or reduced synthesis of type III collagen leads to highly increased fragility of connective tissues resulting in arterial tears or dissections and uterine and/or bowel ruptures as potentially fatal complications.…”
Section: Introductionmentioning
confidence: 99%